Significantly improving the efficiency of communication in paediatrics. (4th April 2011) - Sohi, D; Scotney, E; Sowerbutts, H; Barber, T; Rao, V
Abstract : Introduction: Improving efficiency in healthcare delivery while maintaining patient safety is central to providing high quality patient care, improved patient satisfaction and creates a culture of improved training for future paediatricians. Poor communication during patient handovers has been cited as being one of the most dangerous interventions that clinicians put patients through. The SBAR handover tool has been recognised by the WHO as well as the National Health Service Institute of Innovation and Improvement as a simple and standardised tool that encourages the clinicians to present patient information in a concise and focused fashion that has been shown to improve patient safety. SBAR is an acronym which stands for Situation, Background, Assessment and Recommendation. Aim: To evaluate the impact of time spent by paediatric trainees on the morning patient handover before and after the introduction of SBAR within the department. Method: The handovers involved discussing patients who were on the ward, the ED department, and ambulatory unit. An additional note was made of patients for whom there was a significant psycho-social element to their handover. Information on the time spent discussing each patient using a conventional, semi-structured handover process, was recorded for 7 days (over two consecutive weeks). This was followed by conducting the exercise again after the entire department had undergone SBAR training and a 2 month period of daily practise. Data was then gathered for a 14 day period over three consecutive weeks. Results: Prior to commencing the use of SBAR, each handover was taking an average of 55.7 min (range 40 to 73) with 22 patients being discussed per handover on average. Post SBAR, it took an average of 32 min for each handover (range 19 to 49) with 21 patients being discussed per handover. Pre SBAR, it took an average of 2.57 min to handover a patient compared to 1.54 min post SBAR. This represents a 60% reduction in time using SBAR (p<0.0003). Conclusions: This significant reduction in handover times using SBAR demonstrates improved efficiency. This has several benefits including enabling time to be generated for 'micro-teach' sessions and improved paediatric training or increasing departmental productivity.